Sodium Tanshinone IIA Sulfonate Decreases Cigarette Smoke-Induced Inflammation and Oxidative Stress via Blocking the Activation of MAPK/HIF-1α Signaling Pathway - Guan, Ruijuan; Wang, Jian; Li, Ziying; Ding, Mingjing; Li, Defu; Xu, Guihua; Wang, Tao; Chen, Yuqin; Yang, Qian; Long, Zhen; Cai, Zhou; Zhang, Chenting; et al. (Frontiers in Pharmacology, 2018)
Aberrant activation of hypoxia-inducible factor (HIF)-1α is frequently encountered and promotes oxidative stress and inflammation in chronic obstructive pulmonary disease (COPD). The present study investigated whether sodium tanshinone IIA sulfonate (STS), a water-soluble derivative of tanshinone IIA, can mediate its effect through inhibiting HIF-1α–induced oxidative stress and inflammation in cigarette smoke (CS)-induced COPD in mice. Here, we found that STS improved pulmonary function, ameliorated emphysema and decreased the infiltration of inflammatory cells in the lungs of CS-exposed mice. STS reduced CS- and cigarette smoke extract (CSE)-induced upregulation of tumor necrosis factor (TNF)-α and interleukin (IL)-1β in the lungs and macrophages. STS also inhibited CSE-induced reactive oxygen species (ROS) production, as well as the upregulation of heme oxygenase (HO)-1, NOX1 and matrix metalloproteinase (MMP)-9 in macrophages. In addition, STS suppressed HIF-1α expression in vivo and in vitro, and pretreatment with HIF-1α siRNA reduced CSE-induced elevation of TNF-α, IL-1β and HO-1 content in the macrophages. Moreover, we found that STS inhibited CSE-induced the phosphorylation of ERK, p38 MAPK and JNK in macrophages, and inhibition of these signaling molecules significantly repressed CSE-induced HIF-1α expression. It indicated that STS inhibits CSE-induced HIF-1α expression likely by blocking MAPK signaling. Furthermore, STS also promoted HIF-1α protein degradation in CSE-stimulated macrophages. Taken together, these results suggest that STS prevents COPD development possibly through the inhibition of HIF-1α signaling, and may be a novel strategy for the treatment of COPD.